SKIN THERAPY USING COLD ATMOSPHERIC PLASMA - Jassim, Muntadher Ghanem; Hussein Ali Mujbil; Azhar Awad Jabr; Munif; Mutab Jarad; Karar Khazal Jarad; Hassan Ali Naeem; Ismail Nouri (PT. Antis International Publisher, 2024)
Background: Maintaining skin integrity is essential for protecting against external agents, microorganisms, and dehydration, while also serving social and aesthetic functions. Recent advancements in skin care have introduced innovative technologies, including Cold Atmospheric Plasma (CAP), which shows promising results in dermatology. Specific Background: CAP technology, based on physical principles, has emerged as a novel approach in skin treatments, offering potential benefits for aging prevention and skin care. This interdisciplinary field encompasses physics, biology, chemistry, and biochemistry, presenting a complex landscape. Knowledge Gap: Despite its potential, there is limited comprehensive analysis of CAP's interactions with skin, its effects, and its practical applications in cosmetic dermatology. Aims: This research aims to provide a broad survey of CAP's interactions with skin by discussing the basic structure and functions of the skin, the foundational principles of CAP, and its physical and chemical properties. The study will analyze CAP parameters to highlight known effects and explore potential applications in skin treatment. Results: The review reveals that CAP exhibits versatile applications in dermatology, including direct treatment of superficial lesions, indirect treatment via plasma-activated media, and combined use with other therapies. CAP has shown promise in optimizing intact skin, facilitating transdermal drug delivery, and minimizing side effects. However, challenges remain in integrating CAP into routine clinical practice. Novelty: This overview synthesizes current knowledge and emerging potential of CAP technology in skin biology, offering a comprehensive evaluation of its effects and applications. Implications: The findings underscore CAP's potential to revolutionize skin care and dermatological treatments. Addressing the existing challenges and expanding research could enable CAP to become a valuable tool in both therapeutic and cosmetic dermatology.